Investor Sentiment and Mutual Fund Alpha. Issue 1 (2nd January 2020) - Bu, Qiang
Abstract: The author examines the relationship between investor sentiment and mutual fund alpha. The author finds that investor sentiment plays a significant role in the value and occurring probability of alpha and the probability of earning alpha is high when investor sentiment gets higher. Also, the author finds that a benchmark model adjusted by investor sentiment can significantly reduce the occurring probability of fund alpha. Overall investor sentiment is an essential factor missing in extant benchmark models. A robustness check confirms this finding.